Molecular based detection of Salmonella sp. in selected fish species via multiplex polymeras chain reaction assay / Syifa Shafiqah Abdul Rashid - Abdul Rashid, Syifa Shafiqah (2020)
Multiplex polymerase chain reaction (multiplex PCR) assay offers a very specific multiple detections of target bacteria by amplifying more than one gene in a single assay, which aids directly in reducing cost, energy and time. The target bacteria in this study is Salmonella sp. which comes from family of Enterobacteriaceae. This study aims to implement the molecular-based detection of Salmonella sp. by using specific invA gene and 16S rRNA as the internal amplification control gene through multiplex PCR. The assay used to detect bacteria isolated from fish samples specifically on Salmonella sp. The invA gene was chosen in this study as a specific fragment of Salmonella sp. since it gives this bacteria the ability to invades the intestinal cell of its host. BLAST was performed in both target genes. The specific primer sequence of invA gene was selected since this gene expressed in almost all Salmonella spp., and 16S rRNA was chosen since it presents in almost all gram negative bacteria. The genomic DNA was extracted from bacteria culture of 5 Salmonella sp., 3 other bacteria strains and selected fish species. The optimized condition of multiplex PCR was performed with Ta = 58ºC, MgCl2 = 1.5 mM, dNTPs = 0.25 mM, both invA primers = 0.8μM, both 16S rRNA primers = 0.3 μM and Taq polymerase = 2U. Both 16S rRNA and invA genes were successfully amplified by giving two fragments with size of 478 bp and 254 bp respectively. The specificity test showed 2 bands of 16S rRNA and invA gene were formed for all target bacteria of Salmonella sp., but only single band was formed for all other bacteria strains as non-targeted samples. As a proof-of-concept, bacteria culture isolated from seven fish samples showed none Salmonella sp. as no fragment of invA gene produced. This study was done to provide benefits in term of the detection of pathogenic Salmonella sp. in the food industry by focusing on fish samples.